2022
DOI: 10.1038/s41598-022-25357-1
|View full text |Cite
|
Sign up to set email alerts
|

Possible contribution of COVID-19 vaccination to the subsequent mental well-being in Japan

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has had a severe impact on mental well-being. Vaccination may have played a pivotal role in enduring this mental health crisis. The present study aimed to longitudinally investigate the association between COVID-19 vaccination and mental health status among Japanese population in 2021. Longitudinal data of 17,089 individuals aged 15–79 years who participated in a nationwide online study were analyzed. Baseline and follow-up mental health statuses were assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This is consistent with research among adults in Jordan which found that anxiety symptoms decreased significantly postvaccination among individuals experiencing mild to severe anxiety before COVID-19 vaccination, with greater reductions among those with moderate or severe anxiety compared to mild anxiety [24]. Similarly, among a national cohort of adults in Japan, COVID-19 vaccination was associated with improved mental health among those who reported psychological distress before vaccination [23]. Additional research is needed to better understand the mental health impact of COVID-19 vaccination among individuals with mental health symptoms prior to vaccination.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is consistent with research among adults in Jordan which found that anxiety symptoms decreased significantly postvaccination among individuals experiencing mild to severe anxiety before COVID-19 vaccination, with greater reductions among those with moderate or severe anxiety compared to mild anxiety [24]. Similarly, among a national cohort of adults in Japan, COVID-19 vaccination was associated with improved mental health among those who reported psychological distress before vaccination [23]. Additional research is needed to better understand the mental health impact of COVID-19 vaccination among individuals with mental health symptoms prior to vaccination.…”
Section: Discussionsupporting
confidence: 87%
“…Little remains known about the relationship between COVID-19 vaccination and mental health, and evidence suggests that holding ambivalent attitudes toward vaccination may be related to poor mental health [19,20]. For some, the negative effects of the pandemic on mental health may be reduced with vaccination and the possibility of reduced social isolation and increasing population immunity that comes with vaccination [21][22][23]. This may be particularly relevant for those with greater fear or anxiety related to COVID-19 exposure or illness or for those at greater risk for severe COVID-19 illness [21,23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our models, the following parameters were included age, sex, marital status, educational attainment, smoking status, habitual alcohol intake, number of COVID-19 vaccinations, FCV-19S score, K6 score, comorbidities, household income and participation in the Japan COVID-19 and Society Internet Survey (JACSIS) 2022. 20 In the JASTIS project, the invitation to JASTIS 2023 was addressed primarily to the participants of JASTIS 2022. Furthermore, the invitation was also addressed to former JACSIS participants to attain a designated sample size because the sample selection of the JACSIS and JASTIS were similar.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A survey of 3 million U.S. adults conducted between April 2020 and August 2022 found that levels of anxiety and depression were highest in late 2020, followed by anxiety and depression beginning to decline in early 2021 [ 11 ]. In addition, a longitudinal study of mental health in the Japanese population in 2021 reported that the number of people who were worried about COVID-19 infection decreased from April to June 2021 to October to December 2021 [ 12 ]. However, there are no studies that quantitatively evaluate the mental health status of migrants living in Japan.…”
Section: Introductionmentioning
confidence: 99%